Microsatellite instability in Drosophila spellchecker1 (MutS homolog) mutants. - Flores, C.; Engels, W. (Proceedings of the National Academy of Sciences of the United States of America, 1999)
We have cloned a mutS homolog from Drosophila melanogaster called spellchecker1 (spel1) and have constructed spel1 mutant flies. MutS proteins promote the correction of DNA mismatches and serve important roles in DNA replication, recombination, and repair. The spel1 gene belongs to a subfamily of mutS first characterized by the MSH2 gene of yeast and which also includes hMSH2, one of the two major hereditary nonpolyposis colon cancer loci of humans. Like msh2 mutants in other species, we find that flies lacking the spel1 gene suffer a highly increased rate of instability in long runs of dinucleotide repeats when analyzed after 10-12 fly generations. Using a new assay, we have also discovered that mutations in spel1 decrease the stability of a dinucleotide repeat when it is copied into the site of a double-strand break during gene conversion. Contrary to the case in mammalian cells, spel1 deficiency does not affect tolerance of flies to a methylating agent nor does it affect resistance to gamma-irradiation.